The Determinants of Tax Avoidance with Good Corporate Governance as A Moderating Variable - Prismanitra, Katrin; Sukirman, Sukirman (Accounting Analysis Journal, 2021)
The purpose of this study is to obtain empirical evidence of the impact of earnings management and corporate social responsibility on tax avoidance moderated by good corporate governance (ownership of independent committees, audit committees, and institutions). This study uses secondary data from the population of 49 mining companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2018. The sample selection method is a purposive sampling of 97 analysis units. The data analysis method moderating regression analysis in IBM SPSS version 17.0. As a result, earnings management has a positive effect on tax avoidance and corporate social responsibility has a negative effect on tax avoidance. Good corporate governance, represented by institutional ownership, can moderate (weaken) the impact of earnings management on tax avoidance. The conclusion of this study is that the application of more advanced earnings management improves tax avoidance practices, and more advanced management oversight by institutional owners reduces management opportunity activities and tax avoidance practices. Companies that have expressed their social responsibility pay taxes fairly and have a lower level of avoidance. Keywords: Earnings Management; Corporate Social Responsibility; Good Corporate Governance; Tax Avoidance